Utwór pracowniczy powstały z wykorzystaniem sztucznej inteligencji oraz informacji sektora publicznego - Barański, Michał; Jankowska, Marlena (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The reason for writing this article was the generation (by an algorithm called “Quakebot” written in programming language by the “Los Angeles Times” journalist, Ken Schwencke) of a press release about the earthquake that was registered five miles from Westwood (California, USA) on 23 December 2013. This information was prepared on the basis of the USGS Earthquake Notification Service message posted on the government website. The article formulates the view that the personal nature of employment does not exclude the possibility of creating a work with the use of artificial intelligence. In addition, it was found that the piece of work does not lose its legal character even if it was created with the use of public sector information, as well as that it is acceptable to re-use public sector information for commercial purposes, obtained through Artificial Intelligence.